PERUBAHAN SOSIAL EKONOMI MASYARAKAT DI KELURAHAN GUNUNG SARIK KECAMATAN KURANJI KOTA PADANG - Palmasri, Palmasri; Bakaruddin, Bakaruddin; Zuriyani, Elvi (STKIP PGRI Sumbar, 2013)
This study aims to determine the socio-economic changes of community in Sarik Mount Village district of Kuranji Padang city that includes : 1 ) Livelihood, 2 ) Education and 3 ) land area residents.This research is descriptive. The population in this study were all residents in Sarik Mount Village district of Kuranji Padang city totaling 3,701 households. Samples were taken in 2 ways, with engineering samples taken territory taken by porposive sampling technique (designation) is just taking RW I, RW III , VIII and RW RW X, his appointment basis for 4 to the region which is a region experiencing housing development 56 the number of households, while the sample region taken with total sampling at 56 KK .The research found that: 1) There were changes in the livelihoods of the changes in peoples livelihoods, livelihood development after the livelihood of farmers were 21 respondents ( 37,5 % ), while 24 respondents ( 42,9 % ) switched to merchant and (19,6 % ) and changes to labor income levels before and after the development of housing in Sarik Mount Village district of Kuran ji Padang city in one month, (2) There were changes in family education, especially school dropouts decreased ( from 33.9 % to 7,1 % ) and the cause of children dropping out of school before and after the land turned into housing is the cost factor (33,9% to 5,4% ) and ( 3 ) There is a change in the amount of agricultural land area of 24 hectares, before the development of the average farmers had 1,5 ha and 2 ha ( 33,9%), while after the development of the community who do not have the existing agricultural land (26,8%). Before the agriculture land residential development generally rice (100,0%) and after the development of paddy stay (73.2 % ). Landowners who turns are as many as 19 people with an area of 24 ha